Analisis Contagion Informasi Kenaikan Pajak Warga Amerika Terhadap Indeks Pasar Modal Tujuh Negara Kaya Berkembang - , Aviandi Okta Maulana; , Dr. Sumiyana, M.Si., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research examines contagion effect among seven new emerging economy countries around the incerease of U.S. household tax January2, 2013. Using one minutes intraday return as a data. Johansen cointegration test and Granger causality test is used for knowing contagion relation among study period. The result clearly shows that the increase of U.S. household tax causes contagion relationship among the capital markets and strong relationship between short-term capital market studied.